Leaders Who Changed the 20th Century - Mayberry, Jodine (Raintree Steck-Vaughn Publishers, 1994)
Presents biographical sketches of twenty people who made significant contributions to the history of the twentieth century, including Jane Addams, Ho Chi Minh, Lech Walesa, and Nelson Mandela.
Keywords: Juvenile Nonfiction; Politics & Government Statesmen; Social Science